Antifeminism as an intersectional ideology: reflections on the usefulness of intersectional analyses in the context of the racist instrumentalization of women’s rights - Goetz, Judith (Frontiers in Political Science, 2025)
Using the example of German feminist debates, this paper examines the applicability of intersectional approaches to analyzing the relationship between antifeminism, racism, and sexism, as well as the far-right co-optation of critiques of sexism, using the debates surrounding the evaluation of the sexualized assaults on New Year’s Eve in Cologne 2015/16 as a starting point. First, different positions in the German feminist discourse are outlined, and through a summary of key criticisms of intersectionality theories, the necessity of an identity- and society-critical understanding of intersectionality is developed. After briefly discussing the role of antifeminism within far-right ideology, the paper explores the conceptualization of antifeminism as an intersectional ideology, highlighting its entanglements with other ideologies of inequality and their mutual reinforcement. Drawing on Karin Stögner’s concept of an intersectionality of ideologies, it is argued that an intersectional perspective offers valuable insights for analyzing both antifeminism and far-right instrumentalizations of sexualized violence. The paper concludes with reflections on how these considerations can be linked to political education and potential applications of the findings.